Background differences in baseline and stimulated MMP levels influence abdominal aortic aneurysm susceptibility. Issue 2 (December 2015) - Dale, Matthew A.; Suh, Melissa K.; Zhao, Shijia; Meisinger, Trevor; Gu, Linxia; Swier, Vicki J.; Agrawal, Devendra K.; Greiner, Timothy C.; Carson, Jeffrey S.; Baxter, B. Timothy; Xiong, Wanfen
Abstract: Objective: Evidence has demonstrated profound influence of genetic background on cardiovascular phenotypes. Murine models in Marfan syndrome (MFS) have shown that genetic background-related variations affect thoracic aortic aneurysm formation, rupture, and lifespan of mice. MFS mice with C57Bl/6 genetic background are less susceptible to aneurysm formation compared to the 129/SvEv genetic background. In this study, we hypothesize that susceptibility to abdominal aortic aneurysm (AAA) will be increased in 129/SvEv mice versus C57Bl/6 mice. We tested this hypothesis by assessing differences in aneurysm size, tissue properties, immune response, and MMP expression. Methods: Mice of C57Bl/6 or 129/SvEv background underwent AAA induction by periaortic application of CaCl2 . Baseline aortic diameters, tissue properties and MMP levels were measured. After aneurysm induction, diameters, MMP expression, and immune response (macrophage infiltration and bone marrow transplantation) were measured. Results: Aneurysms were larger in 129/SvEv mice than C57Bl/6 mice (83.0% ± 13.6 increase compared to 57.8% ± 6.4). The aorta was stiffer in the 129/SvEv mice compared to C57Bl/6 mice (952.5 kPa ± 93.6 versus 621.4 kPa ± 84.2). Baseline MMP-2 and post-aneurysm MMP-2 and -9 levels were higher in 129/SvEv aortas compared to C57Bl/6 aortas. Elastic lamella disruption/fragmentation and macrophage infiltration were increased in 129/SvEv mice. Myelogenous cell reversal by bone marrow transplantation did not affect aneurysm size. Conclusions: These data demonstrate that 129/SvEv mice are more susceptible to AAA compared to C57Bl/6 mice. Intrinsic properties of the aorta between the two strains of mice, including baseline expression of MMP-2, influence susceptibility to AAA.